2020
DOI: 10.18231/j.ijceo.2020.091
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative parameter assessment in peri-presbyopic early onset diabetics with age matched healthy individuals - A case control study

Abstract: To compare various accommodative parameters in peri-presbyopic diabetic patients with age-matched healthy individuals.To compare Four Accommodative parameters in peri-presbyopic early onset diabetic patients and age matched non-diabetic individuals.1. To compare and analyse Four accommodative parameters in peri-presbyopic early onset diabetics with that of peri-presbyopic age matched non-diabetic individuals (35-45; years); 2. To analyse the effect of treatment / metabolic control on the parameters. 3. To obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 5 publications
4
7
1
Order By: Relevance
“…As mentioned earlier, most previous studies focused on the AA, and the effects of DM on other accommodative parameters including AF and AR have been investigated less frequently. In line with the findings of the present study, Sridhar and Ramachandra reported a significantly lower mean AF in young diabetics compared to the control group (5.12 vs. 10.68 cpm) 15 . Additionally, in an investigation by Abokyi et al on young adults with DM, subjects with a higher fasting plasma sugar level (FBS > 7 mmol/L) had a significantly higher accommodative lag than those with a lower FBS (≤7 mmol/L).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As mentioned earlier, most previous studies focused on the AA, and the effects of DM on other accommodative parameters including AF and AR have been investigated less frequently. In line with the findings of the present study, Sridhar and Ramachandra reported a significantly lower mean AF in young diabetics compared to the control group (5.12 vs. 10.68 cpm) 15 . Additionally, in an investigation by Abokyi et al on young adults with DM, subjects with a higher fasting plasma sugar level (FBS > 7 mmol/L) had a significantly higher accommodative lag than those with a lower FBS (≤7 mmol/L).…”
Section: Discussionsupporting
confidence: 92%
“…In line with the findings of the present study, Sridhar and Ramachandra reported a significantly lower mean AF in young diabetics compared to the control group (5.12 vs. 10.68 cpm). 15 Additionally, in an investigation by Abokyi et al on young adults with DM, subjects with a higher fasting plasma sugar level (FBS > 7 mmol/L) had a significantly higher accommodative lag than those with a lower FBS (≤7 mmol/L). Moreover, the insulin control of DM for 3 months was associated with a significant reduction in the mean accommodative lag from 1.37 to 0.87 D (p < 0.001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, Etezad et al 31 found significantly higher PRA in a T1D group compared with controls, whereas here, similar values were found in the two groups, consistent with Srihard and Ramachandra. 9 It should also be noted that there were significant differences in age between the two groups of participants in Etezad et al 31 However, as NRA and PRA are measured under binocular conditions, they are tests of both the accommodative and vergence system, and therefore should only be considered as supplementary tests in the diagnosis of accommodative disorders.…”
Section: Discussionmentioning
confidence: 97%
“…6 With regard to accommodation in individuals with diabetes, as a product of hyperglycaemia the proteins of the lens are lost, leading to a decline in elasticity and the ability to focus on near objects. Therefore, some authors have suggested that these subjects have decreased accommodative power for their age compared with patients without diabetes, [7][8][9][10] and in some cases, these changes are related to glycaemic control, with contradictory results in this regard. [11][12][13] Variations within the crystalline lens could lead to accommodative disorders, that is, visual disturbances that affect the subject's binocular vision and visual performance, particularly when performing near-vision tasks.…”
mentioning
confidence: 99%